Peningkatan Ketrampilan Penggunaan Microsoft Office Bagi Guru SD N 104276 Kebun Ubi - Nora Anisa Br Sinulingga; Hendy Irwanda; Bella Monika (Cv. Utility Project Solution, 2023)
The development of information technology does not only play a role in the economic sector but also in the education sector. Today every teacher at almost all levels of education is required to be literate in technology, especially information technology. In addition to supporting educational activities, information technology literacy also supports teachers in solving administrative problems. One of the software that can be used to support education and administrative issues is Microsoft Word, Microsoft Word software, has many features that are still not familiar to some users, especially elementary school (SD) teachers. This was experienced by the teachers of SD N 104276 Kebun Ubi who were not familiar with the many tools provided in software such as Microsoft Word. Some of the obstacles that are often encountered are the lack of maximum use of referencing tools in Microsoft Word. This is the background for the service team to provide training on